First observation of the decay B s 0→K *0K̄ *0 - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; et al. (2012)
The first observation of the decay B s 0→K *0K̄ *0 is reported using 35 pb -1 of data collected by LHCb in proton-proton collisions at a centre-of-mass energy of 7 TeV. A total of 49.8±7.5 Bs0→(K +π -)(K -π +) events are observed within ±50 MeV/c 2 of the B s 0 mass and 746 MeV/c 2